CIFOR - using a 'system' approach to research evaluation - Spilsbury, M.J. (CGIAR Technical Advisory Committee, 2001)
The overarching objective for CIFOR is to ensure that research activities result in significant impacts. A secondary, but very important, requirement is to be able to measure and quantify impact. However, impact assessment at CIFOR is viewed as a component in the broader frame of research evaluation and within the dynamic system of identifying problems, planning solutions, producing outputs, promoting adoption, and securing positive outcomes in line with its mission. In the context of this changing environment, adaptation and learning are key institutional requirements. This paper describes CIFOR's work in relation to impact assessment and research evaluation more generally. It explores the rationale and strategy of the CIFOR programme on research impacts and describes key concepts such as "impact pathways", and efforts to foster an 'impact culture' within the organisation. Constraints, opportunities and other important issues in relation to impact assessment at CIFOR are also highlighted.